ANALISIS MAKNA TERHADAP BARANG BRANDED THRIFTING OLEH GENERASI Z: STUDI KASUS PEMBELI DI PASAR PANORAMA KOTA BENGKULU - Wijayanti, Ayu; Gustina, Rina (JURNAL ILMIAH IDEA, 2024)
This study aims to describe the meaning of generation Z towards branded thrifting goods. This study uses a qualitative research method with a case study approach, namely generation Z who buy branded thrifting goods at Pasar Panorama. In this study, researchers used the snowball technique to obtain informants, where researchers obtained informants through recommendations by key informants. The data for this study were obtained through data collection techniques, namely observation, interviews, and documentation which were analyzed through the stages of data reduction and presentation. Research results Based on the results of research that has been conducted on the phenomenon of thrifting, it was found that generation Z interprets branded thrifting goods as a symbol in increasing their social status, and providing recognition from society and as a place to express themselves. The researcher’s findings show that generation Z is not only interested in the functional aspects of the goods, but also the symbolic value attached to the brand. By using branded goods from thrifting, they can express themselves and show an upper-class image